First descriptions of the seasonal habitat use and residency of scalloped hammerhead (Sphyrna lewini) and Galapagos sharks (Carcharhinus galapagensis) at a coastal seamount off Japan - David M. P. Jacoby; Yuuki Y. Watanabe; Tre Packard; Mark Healey; Yannis P. Papastamatiou; Austin J. Gallagher (Animal Biotelemetry, 2022)
Abstract Background The Northwestern Pacific is a data-poor region for studies into the movements and habitat use of open ocean and pelagic sharks. However, this region experiences considerable pressure from commercial fishing. Therefore, shark movement data from this region carry significant implications for conservation and management, particularly for threatened species. Here, we provide the first data on seasonal residency and movements of scalloped hammerhead (Sphyrna lewini) and Galapagos sharks (Carcharhinus galapagensis), using acoustic and satellite telemetry, and dive logbooks, off Japan. Results Eight female sharks, four of each species, were tagged around a coastal seamount off southeastern Japan (Mikomoto Island) in August 2015, and monitored for a period of up to 363 days using an array of six receivers around the island. Analyses of the more abundant scalloped hammerhead acoustic data suggest high seasonal residency predominantly from August to November associated with lower chlorophyll-a concentrations, before sharks then leave the island and return the following summer. Residency for scalloped hammerhead sharks were highest among those receivers closest to the Kuroshio Current, which produces strong coastal upwelling, however SST was not found to be predictive of occurrence at Mikomoto. Shark presence was corroborated by analysis of dive-log data from a local ecotourism operator. We also produced two unique satellite tracks, whereby a scalloped hammerhead exhibited a 200-km dispersal into a coastal embayment west of the tagging location and a Galapagos shark migrated over 800 km offshore into the high seas. Conclusion This study provided some of the first behavioral and movement data for scalloped hammerhead and Galapagos sharks in Japan. Our findings suggest varying spatial and temporal visitation of two shark species to a coastal seamount, underscored by some degree of seasonal residency and site fidelity and linked, for scalloped hammerhead sharks at least, to varying productivity. Furthermore, we provided preliminary evidence for long-distance dispersal of these species, and some site fidelity to seamounts in the region. This study highlights the importance of describing shark movements to aid in filling critical data gaps for poorly understood, endemic populations of threatened species.